Solar energy: direct and indirect methods to harvest usable energy - Adarsh Kumar, Pandey; Reji, Kumar. R; M., Samykano (Science Direct, 2021)
The global energy demand is increasing substantially due to increasing population, industries, and technological development. The renewable energy sources can play vital role to cope up with the rising demand for energy and reduce greenhouse gas emissions. Solar radiation is a source of renewable energy from sun, and it can generate electrical and heat energies using appropriate harvesting techniques [1]. The solar energy can be employed in two forms, which are solar thermal and photovoltaics. The solar energy can be directly converted into electricity (by solar photovoltaics) or indirectly converted into heat energy (by solar thermal collectors). Although photovoltaic (PV) requires high capital cost, this technology is accepted worldwide due to less maintenance and operating cost.